The Increasing The Competency of Chemical Teachers Of South Coast Regency To Prepare Students At The National Science Olimpiade - Sri Benti Etika (Fakultas MIPA Universitas Negeri Padang, 2020)
Training activities have been carried out to improve the competence of chemistry MGMP teachers in Pesisir Selatan district in preparing students to take part in Nasional Science Olimpiade (NSO) . So far, it is known that very few students qualify for NSO coming from the South Coastal district. One of the obstacles faced by schools in Pesisir Selatan district is the lack of adequate resources because problems in NSO require in-depth mastery of the material. Based on the results of the analysis of pretest and posttest in general the value of MGMP Chemistry teachers in Kab. Pesisir Selatan in general increased with an average value of 38.1. Although it did not increase significantly, this training was considered to have a positive impact on teachers with an average evaluation score of the activity of 3.48.